Metaphorical materialism : art in New York in the late 1960s - Rahtz, Dominic (Studies in art & materiality, 2021)
"In Metaphorical Materialism: Art in New York in the Late 1960s, Dominic Rahtz returns to a period when the materiality of art was thematized and theorized according to varying conceptions of matter and form, and consciously related to materialisms held as wider philosophical and political positions and attitudes. The book consists of a volume of essays on the relationships between materiality and materialism, informed by definitions of labour, process, corporeality, and language, in the work of Carl Andre, Robert Smithson, Richard Serra, Eva Hesse and Lawrence Weiner"--